MARKET STRATEGY AND MARKET SEGMENT - Mariesta Reny Tonapa; Marselinus Asri; Bernadeth Tongli (AJAR, 2020)
This study aims to study how the marketing strategies of advertising, products, prices and channels affect the financial performance of Novotel Makassar Hotel. The sample used in this study is clients who book rooms and meeting rooms at the Novotel Makassar Hotel. The selection of samples in this study using a survey method based on certain criteria. The results of the study using path analysis show marketing strategies namely advertising, products, prices and positive distribution channels on financial performance.